2005
DOI: 10.1021/jm050758z
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lavendamycin Analogues as Antitumor Agents:  Synthesis, in Vitro Cytotoxicity, Structure−Metabolism, and Computational Molecular Modeling Studies with NAD(P)H:Quinone Oxidoreductase 1

Abstract: Novel lavendamycin analogues with various substituents were synthesized and evaluated as potential NAD(P)H:quinone oxidoreductase (NQO1)-directed antitumor agents. Pictet-Spengler condensation of quinoline- or quninoline-5,8-dione aldehydes with tryptamine or tryptophans yielded the lavendamycins. Metabolism studies with recombinant human NQO1 revealed that addition of NH2 and CH2OH groups at the quinolinedione-7-position and indolopyridine-2'-position had the greatest positive impact on substrate specificity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 64 publications
4
78
0
Order By: Relevance
“…Notably, the 5,8-quinolinequinone, streptonigrin and its derivatives have demonstrated anti-cancer activities (1). Similar 5,8-quinolinequinones have been reported to have anti-bacterial, anti-malarial, anti-fungal, and anti-inflammatory activities (2–7). Another quinolinequinone, LY83583 (6-anilino-5,8-quinolinequinone), has been shown to inhibit soluble guanylate cyclase and leukotriene synthesis with IC50 concentrations in the 1–2 micromolar range (8–9).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Notably, the 5,8-quinolinequinone, streptonigrin and its derivatives have demonstrated anti-cancer activities (1). Similar 5,8-quinolinequinones have been reported to have anti-bacterial, anti-malarial, anti-fungal, and anti-inflammatory activities (2–7). Another quinolinequinone, LY83583 (6-anilino-5,8-quinolinequinone), has been shown to inhibit soluble guanylate cyclase and leukotriene synthesis with IC50 concentrations in the 1–2 micromolar range (8–9).…”
Section: Introductionmentioning
confidence: 58%
“…Notably, streptonigrin and its derivatives have been studied for more than five decades as potential anti-cancer agents (1). The structurally related lavendamycin has been the subject of investigation for both its anti-cancer and antibiotic activities (23). Similar quinolinequinones have been reported to have potent anti-inflammatory and anti-fungal properties (19), and LY83583 has been identified as a specific inhibitor of soluble guanylate cyclase (7–9).…”
Section: Discussionmentioning
confidence: 99%
“…Although unusual, higher rates for acetylated analogues have been observed in other series. 6, 11 With regard to the aromatic substituents at the quinoline-2-position, no clear trend in reduction rates was observed except that bulkier groups generally decreased reduction rates. Oxygen consumption is a measure of the ability of the reduced quinone (hydroquinone) to redox cycle following reduction by NQO1.…”
Section: Resultsmentioning
confidence: 93%
“…2-Aldehyde-8-hydroxyquinoline (ahq) was synthesized according to the reported method [22], and tris(hydroxymethyl)aminomethane (tris) was commercially purchased. The ligands N-(2-(8-hydroxylquinolinyl)methylene)(trishydroxymethyl)methylamine (Hnhm) and 2,8-bis(2-(8-hydroxylquinolinyl))-1-aza-5-hydroxymethyl-3,7-dioxabicyclo[3.3.0]octane (H 2 baho) were in-situ formed.…”
Section: Materials and General Methodsmentioning
confidence: 99%
“…Especially, it is recently reported that 2-aldehyde-8-hydroxyquinoline could efficiently sensitize Yb 3+ ions, where intriguing NIR photoluminescence has been observed [15][16][17][18]. We have reported the syntheses, structures and NIR luminescence of a series of Nd 3+ and Yb 3+ complexes coordinated with 2-(2 0 -hydroxyphenyl)benzimidazole, and salen-type ligands, respectively [19][20][21][22]. As a continuing attempt for NIR property, we herein present the syntheses, structures of a series of mononuclear lanthanide complexes Ce(baho) 2 ÁEt 2 O (1), Dy(nhm) 2 ClÁ0.5H 2 O (2) and Ln(nhm) 2 ClÁ0.5C 6 H 14 (Ln = Ho (3), Er (4), Yb (5)) ( Fig.…”
Section: Introductionmentioning
confidence: 94%